Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/en15061955
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Crude Oil Prices with a WT-FNN Model

Abstract: In order to improve the accuracy of forecasting crude oil prices, a new crude oil price forecasting method is introduced in the paper that is a combination of the FNN model and the stochastic time effective function—namely, the WT-FNN model. The FNN model keeps track of the historical values of crude oil prices and predicts future crude oil prices, and the stochastic time effective function gives greater weight to recent information and smaller weight to old information, thus making the prediction of crude oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In the literature, many publications can be found related to forecasting the demand for fossil resources, but only a small part of the articles concern forecasting the demand for crude oil. There are many ways of forecasting the demand for energy resources, autoregressive and moving average (ARMA) models [84,85], generalized ARCH model [86], models of the stochastic effective function [87], and methods of forecasting time series through artificial neural networks [88][89][90]. Table 3 summarizes existing research on fossil fuel consumption forecasting.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, many publications can be found related to forecasting the demand for fossil resources, but only a small part of the articles concern forecasting the demand for crude oil. There are many ways of forecasting the demand for energy resources, autoregressive and moving average (ARMA) models [84,85], generalized ARCH model [86], models of the stochastic effective function [87], and methods of forecasting time series through artificial neural networks [88][89][90]. Table 3 summarizes existing research on fossil fuel consumption forecasting.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the sentimentbased machine learning models outperformed traditional time-series models like ARIMA and GARCH, indicating the effectiveness of using investor sentiment and machine learning for crude oil futures price prediction. Wang and Fang proposed a method for crude oil price forecasting called WT-FNN, which uses a wavelet transform-based fuzzy neural network (Wang and Fang, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In-sample and out-of-sample performance comparisons revealed that the s-PCA model was superior to the compared models. Wang & Fang [30] developed a novel combination of the FNN model and stochastic time effective function for crude oil prices forecasting, i.e., the WT-FNN model, and the findings revealed that the WT-FNN model had the best predictive impact. Zhang et al [15] offered a novel hybrid technique to predict crude oil prices based on the least square support vector machine, particle swarm optimization, and GARCH model.…”
Section: Forecasting By Hybrid Modelsmentioning
confidence: 99%